State of industrial/organizational psychology in the Philippines - Hechanova, Ma. Regina (Archīum Ateneo, 2005)
This article traces the roots of IO Psychology. Based on archival data,interviews and a review of literature, it presents the state of education,research and practice in IO psychology. The articles highlights the challengesthat IO psychologists face and the implications for the growth of the field inthe country.